2022
DOI: 10.1002/hsr2.833
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices related to COVID‐19 infection, related behavior, antibiotics usage, and resistance among Syrian population: A cross‐sectional study

Abstract: Background and Aims Antibiotic resistance is seen as a worldwide health risk as a result of the overuse of antibiotics. Many countries noted that antibiotic usage was high during the COVID‐19 pandemic. The purpose of this study is to evaluate Syrians' knowledge, attitudes, and practice about the use of antibiotics and antibiotic resistance during the COVID‐19 epidemic. Methods A cross‐sectional study was conducted using an online questionnaire to collect the data from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…For example, in a study by Pogurschi et al, the authors reported that the Romanian population was not disciplined enough when it comes to completing antibiotic treatments, as 29.2% of the respondents indicated they would stop the course of antibiotics if their symptoms improved [15]. In a cross-sectional study of 2406 Syrian respondents, a high proportion of the citizens (65.3%) were aware that antibiotic resistance will spread faster as a result of improper antibiotic usage [29]. Recently, in a survey of 15,526 Chinese antibiotic users, Yin et al revealed that 53.3% of the respondents were non-adherent to antibiotic treatment, and the most commonly observed non-adherence behaviour was discontinuing antibiotics early (78.0%), followed by missing antibiotics (48.3%), decreasing antibiotic dosage (25.5%) and increasing antibiotic dosage (15.2%) [30].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study by Pogurschi et al, the authors reported that the Romanian population was not disciplined enough when it comes to completing antibiotic treatments, as 29.2% of the respondents indicated they would stop the course of antibiotics if their symptoms improved [15]. In a cross-sectional study of 2406 Syrian respondents, a high proportion of the citizens (65.3%) were aware that antibiotic resistance will spread faster as a result of improper antibiotic usage [29]. Recently, in a survey of 15,526 Chinese antibiotic users, Yin et al revealed that 53.3% of the respondents were non-adherent to antibiotic treatment, and the most commonly observed non-adherence behaviour was discontinuing antibiotics early (78.0%), followed by missing antibiotics (48.3%), decreasing antibiotic dosage (25.5%) and increasing antibiotic dosage (15.2%) [30].…”
Section: Discussionmentioning
confidence: 99%
“…A study from Syria analysing knowledge of antibiotic usage during COVID-19 found that there was a statistically significant difference between males and females. They noted that males had better knowledge about antibiotic usage during COVID-19 (p=0.023) [ 29 ]. This data raises the need for a better awareness campaign through print, electronic and digital media during a pandemic.…”
Section: Discussionmentioning
confidence: 99%